Compliance with malaria chemoprophylaxis over a five-year period among children in a rural area of The Gambia. - Allen, S; Snow, R; Menon, A; Greenwood, B (1990)
We have reviewed a malaria chemoprophylaxis programme in which Maloprim (pyrimethamine and dapsone) has been administered fortnightly by village health workers (VHWs) to approximately 1500 children each year aged 6-59 months resident in 15 primary health care villages in a rural area of The Gambia over 5 years. Reasonable levels of compliance with chemoprophylaxis have been maintained by many children over this period. this has occurred despite minimal outside supervision and support of the programme. Factors which may have affected the level of compliance in individual villages are identified. Large villages and those where social or political factionalism were evident tended to have low levels of compliance. The attitudes of VHWs and mothers to the programme were determined. Most VHWs cooperated enthusiastically and kept accurate records of compliance, despite receiving no compensation from the villagers for administering chemoprophylaxis. The administration of a drug to prevent illness in children was complementary to the curative service provided by VHWs. The chemoprophylactic was widely acceptable and nearly all mothers stated that the tablets were good for their children's health. However, knowledge of the specific purpose of chemoprophylaxis in the prevention of malaria was limited. Improvements in the programme which may result in higher levels of compliance are discussed.